An in-depth evaluation of acalabrutinib for the treatment of mantle-cell lymphoma. (2nd January 2020) - Morabito, Fortunato; Recchia, Anna Grazia; Vigna, Ernesto; Botta, Cirino; Skafi, Mamdouh; Abu-Rayyan, Mohammed; Atrash, Moien; Galimberti, Sara; Morabito, Lucio; Al-Janazreh, Hamdi; Martino, Massimo; Cutrona, Giovanna; et al.
ABSTRACT: Introduction : Regimens involving intensive immuno-chemotherapy, followed by high-dose therapy and autologous stem cell transplant represent the standard treatment for younger fit patients with mantle cell lymphoma (MCL). Targeted approaches (i.e. ibrutinib, bortezomib, and lenalidomide) represent the backbone of therapy for relapsed cases. Areas covered : Acalabrutinib is a novel small molecule with a butynamide moiety specifically designed to irreversibly inhibit Bruton tyrosine kinase (BTK), which is more potent and selective than ibrutinib. Relevant publications have been identified through literature searches using the terms 'mantle cell lymphoma' and 'acalabrutinib'. Expert opinion : Acalabrutinib has been approved for the treatment of relapsed/refractory (RR) MCL patients. To date, clinical trials have reported some adverse effects such as cardiac toxicity or atrial fibrillation. Acalabrutinib in combination with other drugs, either in chemo-containing or chemo-free schedules, represent a valid option for MCL. However, none of the treatment schedules containing BTK inhibitors have been shown to be curative in MCL. Acalabrutinib may ultimately represent an option for patients who are 'fit' and exhibit well-controlled disease, which often characterizes only a limited 'niche' among MCL patients.